Mezi Hvězdou a Půlměsícem - Otec uprchlíků . Between a Star and a Crescent - Father of the Refugees - Bok, Petr; Smok, Martin (Vera Film, 2004)
In the summer of 1967 the body of Charles Jordan, a man who wanted to change the very core of the conflict in the Middle East, was fished out of the Vltava river in Prague. His death remains a mystery to this day. The filmmakers discovered new details about the case, while the Czech detectives are still unsuccessfully investigating it.